The Effect of Inflation and Currency Exchange Rates on Stock Price of Cigarette Sub-Sector on the Indonesia Stock Exchange - Arfianty Arfianty; Fatimah Fatimah; Selfy Maulidya (UNEJ e-Proceeding, 2021)
This research aims to determine the relationship between the level of inflation and the Rupiah exchange rate against the US Dollar to share prices partially and simultaneously in the cigarette sub-sector listed on the Indonesia Stock Exchange. This study uses a quantitative approach to data testing, descriptive analysis between variables and, verification analysis to test and determine the magnitude of the influence of the variable between inflation and currency exchange rates on HM Sampoerna TBK's cigarette sub-sector share prices on the Indonesia Stock Exchange for the 2017-2019 period. The research conclusion based on testing obtained for the significance value of inflation on stock prices is 0.434> 0.05, so it can be concluded that H1 is rejected, which means that there is no significant effect of inflation on stock prices. It was known that the significance value for currency exchange rates on stock prices is 0.000 < 0.05. So it can be concluded that H2 is accepted, which means there is a significant influence between currency exchange rates on stock prices. The coefficient of determination (R2) of the inflation and exchange rate variables can explain the share price of 75.3%. Keywords: Currency Exchange Rates, Inflation, Share Prices.